Study of some Structural and optical Properties of Au films prepared by glow discharge sputtering - G. Mohammed, Layla; A.Khudair, Abdul Hussain; H. Wanas, Ahmed (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper, Au thin films have been prepared by using glow discharge sputtering method on a glass substrates with thickness 190nm,270nm and 380nm and studying its structural properties used x-rays diffraction for diagnostic structure and nature thin film material The results showed that the films have a polycrystalline structure and increase thickness led to increase the homogeneity of the thin film and increase of crystallization. Also The optical properties of prepared films have been studied in the UV-VIS region of the electromagnetic spectrum by recording of absorbance and transmittance spectrum of the wavelengths range (300-1100) nm and then the expense of reflectivity spectra and optical constants such as absorption coefficient, extinction coefficient and refractive index calculated as a function of the avelenght ,has been found that the absorbance is getting an increase of thickness while lower transmittance.